Drug Wars and Covert Netherworlds The Transformations of Mexico's Narco Cartels. - Creechan, James H. (University of Arizona Press, 2021)
"Drug Wars and Covert Netherworlds describes the history of Mexican narco cartels and their regional and organizational trajectories and differences. Covering more than five decades, sociologist James H. Creechan unravels a web of government dependence, legitimate enterprises, and covert connections"--